Guided Mindfulness of Death to Reduce Fear of Death in Cancer Patients: Randomized Controlled Study - Seng Beng, Tan; Yong Wen, Leow; Siew Yoong, Ng; Noor Elyna, Mohd Abdul Latif; Mohamad Iqbal, Mohamed Sanaf; Wei Jing, Chua; Chen Joyce, Yong; Diana Leh Ching, Ng; Chee Shee, Chai (Elsevier Inc, 2025)
Objectives: This study aimed to assess the effectiveness of guided mindfulness of death in reducing fear of death in cancer patients.